Teacher organization in Turkey and TÖB-DER in the 1970s - Meseci-Giorgetti, Filiz; Ceven, Gozde (FAHRENHOUSE, 2024)
This study aims to reveal the activities of the All-Teachers' Union and Solidarity Association (T & Ouml;B-DER), one of the most influential education associations between 1971 and 1980, to achieve the goals determined in its statute. The study attempts to answer two fundamental questions about the association's mission and the activities it intends to carry out. The first question is what the organization undertakes to ensure organizational cohesion. The second question is what the association does to tackle the professional concerns of education service employees and ensure their professional development. In this study, document analysis was used as a qualitative research technique. The authors analysed the work programs, by-laws and regulations, reports, documents of the congress, journals, and the work programs of the provincial organizations, as well as brochures and declarations prepared by the central organization of T & Ouml;B-DER. The findings for the first question show that T & Ouml;B-DER increased the number of members and branches, ensuring that teachers and the public attend regional and branch meetings, and informing about the importance of the organization through seminars and forums. The findings for the second question demonstrate that T & Ouml;B-DER organized meetings on solutions for teachers' professional issues and needs, used bulletins, magazines, newspapers, brochures, and leaflets as a source, and conveyed the solution suggestions and demands put forward in these publications to the relevant institutions and the public. This study concluded that T & Ouml;B-DER activities succeeded in raising awareness of the organization to a certain extent in the field of education but were limited in bringing solutions to teachers' professional problems.
Keywords: the 1970s; Turkey; teacher organizations; T & Ouml; B-DER; union; association; Education & Educational Research